2015
DOI: 10.1155/2015/540154
|View full text |Cite
|
Sign up to set email alerts
|

Morphine for the Treatment of Pain in Sickle Cell Disease

Abstract: Pain is a hallmark of sickle cell disease (SCD) and its treatment remains challenging. Opioids are the major family of analgesics that are commonly used for treating severe pain. However, these are not always effective and are associated with the liabilities of their own. The pharmacology and multiorgan side effects of opioids are rapidly emerging areas of investigation, but there remains a scarcity of clinical studies. Due to opioid-induced endothelial-, mast cell-, renal mesangial-, and epithelial-cell-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 103 publications
1
34
0
Order By: Relevance
“…Morphine, an opioid, has been the drug of choice for the treatment of severe pain associated with SCA. 1,2 However, morphine is highly histaminergic, and is known to activate mast cells. 2 We showed earlier that mast cells contribute to neurogenic inflammation and hyperalgesia in sickle mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphine, an opioid, has been the drug of choice for the treatment of severe pain associated with SCA. 1,2 However, morphine is highly histaminergic, and is known to activate mast cells. 2 We showed earlier that mast cells contribute to neurogenic inflammation and hyperalgesia in sickle mice.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, morphine is highly histaminergic, and is known to activate mast cells. 2 We showed earlier that mast cells contribute to neurogenic inflammation and hyperalgesia in sickle mice. 3 We also found that cannabinoids mitigate chronic and hypoxia/reoxygenation (H/R)-evoked acute hyperalgesia in sickle mice.…”
Section: Introductionmentioning
confidence: 99%
“…[23,24] Opioids may even produce severe pathological changes in SCD patients that could contribute to organ damage. [25] More targeted treatment options could reduce the need for opioids, and their harmful side effects.…”
Section: Current Clinical Treatment Of Scd-associated Painmentioning
confidence: 99%
“…On the other hand opioids can cause side-effects including constipation, respiratory depression and mast cell activation involving peripheral and central mechanisms, and the possibility of addiction. 4 Of significance to the tumor microenvironment and inflammation, opioids interact with endothelium, tumor cells, and inflammatory cells via opioid receptor (OP-R) and non-OP-R mediated mechanisms. 5,6 In the peri-operative setting replete with inflammation, opioids can thus modulate the process of metastasis, which is dependent upon angiogenesis, tumor cell survival and inflammation.…”
Section: Introductionmentioning
confidence: 99%